Secondary trauma and burnout in military behavioral health providers beyond the battlefield - Benight, Charles C. (Palgrave Macmillan, 2016)
This book provides an in-depth look at the complex clinical, individual, and organizational challenges that our clinicians face in treating our returning soldiers struggling with the aftermath of more than a decade of war.